Microalgae in Microwell Arrays Exhibit Differences with Those in Flasks: Evidence from Growth Rate, Cellular Carotenoid, and Oxygen Production - Zhang, Ping; Xiao, Yan; Li, Zhe; Guo, Jinsong; Lu, Lunhui (Frontiers in Plant Science, 2018)
Microalgae are cultivated in macro-scale reactors traditionally and the relevant knowledge is based on bulk analysis and macro-sale. Whether the knowledge and laws are true for cells under micro-cultivation is still unknown. To better understand microalgal physiology, micro-cultivation of microalgae and unicellular tracking and analysis in vivo is necessary. In the study, cellular responses of Chlorella vulgaris to micro-cultivation is studied, with cells in flasks as a control. Five different microwell depths ranging from 10 to 200 μm with a fixed diameter of 100 μm, and four diameter levels from 30 to 200 μm with a fixed depth 60 μm were investigated. Unicellular dynamics showed that cell number differences among various types of microwells with different initial cell numbers decreased as cultivation processed. The specific growth rate of C. vulgaris on microwell arrays was much higher than that in flasks thus may be used in cell sensor applications to enhance the sensor sensitivity. It decreased gradually as the microwell diameter increased from 30 to 200 μm and presented a unimodal trend as depth decreased from 200 to 10 μm. Furthermore, we used Raman Spectroscopy and Non-invasive Micro-test Technique to analyze cellular responses in microwells for the first time to track the changes in vivo. Unicellular carotenoid content increased as microwells became larger and shallower. The flow rate of oxygen rose gradually as the depth increased to 100 μm, but then decreased rapidly as it deepened to 200 μm. In fact, it is a comprehensive result of cell physiology and density. In summary, cells in microwells with the diameter/depth ratio approximately 1 owned the highest specific growth rates and oxygen flow rates. Simulations suggested that sufficient mass transfer occurred in microwells with higher diameter-to-depth ratios.